Comparing the Device Physics and Morphology of Polymer Solar Cells Employing Fullerenes and Non‐Fullerene Acceptors. Issue 12 (23rd April 2014) - Bloking, Jason T.; Giovenzana, Tommaso; Higgs, Andrew T.; Ponec, Andrew J.; Hoke, Eric T.; Vandewal, Koen; Ko, Sangwon; Bao, Zhenan; Sellinger, Alan; McGehee, Michael D.
<x xml:space="preserve">Abstract</x> There is a need to find electron acceptors for organic photovoltaics that are not based on fullerene derivatives since fullerenes have a small band gap that limits the open‐circuit voltage (VOC), do not absorb strongly and are expensive. Here, a phenylimide‐based acceptor molecule, 4, 7‐bis(4‐(N‐hexyl‐phthalimide)vinyl)benzo[c]1, 2, 5‐thiadiazole (HPI‐BT), that can be used to make solar cells with VOC values up to 1.11 V and power conversion efficiencies up to 3.7% with two thiophene polymers is demonstrated. An internal quantum efficiency of 56%, compared to 75–90% for polymer‐fullerene devices, results from less efficient separation of geminate charge pairs. While favorable energetic offsets in the polymer‐fullerene devices due to the formation of a disordered mixed phase are thought to improve charge separation, the low miscibility (<5 wt%) of HPI‐BT in polymers is hypothesized to prevent the mixed phase and energetic offsets from forming, thus reducing the driving force for charges to separate into the pure donor and acceptor phases where they can be collected.